Penerapan Ajaran Tri Kaya Parisudha Di SDN 6 Gianyar Dalam Upaya Membentuk Kepribadian Siswa - Prayoga, Ida Bagus Priya (Metta : Jurnal Ilmu Multidisiplin, 2021)
Along with the increasingly rapid development of the globalization era, the implementation of the existing education process is often less appropriate to the conditions the real conditions that occur. The lack of character education implemented by educational institutions is the main factor in having a significant impact on the decline in positive behaviour and noble personality of students towards their environment. In fixing this phenomenon, education of religion, especially Hinduism, has an important role in directing students to have noble character in living their lives in society. In the reality, Hindu learning can be used as the foundation, thought and the spirit of education which leads to social, ethical and moral values in building cultured Hindu people. The implementation of Hindu learning, it is Tri Kaya Parisudha, teaches Hindu people to behave (kayika), speak (wacika) and think (manacika) well and correctly. In the ongoing research process, several problems were formulated, including: (1) How to implement the teachings of Tri Kaya Parisudha in shaping SDN 6 Gianyar students' personalities. (2) What are the obstacles faced in implementing the Tri Kaya Parisudha in shaping SDN 6 Gianyar student personality. The purpose of carry out this research is to determine the extent of the positive impact of implementing the Tri Kaya Parisudha in shaping SDN 6 Gianyar students' personalities. Furthermore, the research method used in this case study is a type of qualitative research with the source of the qualitative data and equipped with primary and secondary data sources with data collection methods, there are observation, interviews, literature study and documentation. From the ongoing research process, there are related research results which show that the application of Tri Kaya Parisudha teachings to the children, especially the students of SDN 6 Gianyar, has a significant impact on efforts to shape students' character and personality. Therefore, it can be concluded that moral and character education through learning about Hinduism, especially the Tri Kaya Parisudha teachings, is very important to instill in children from an early age to foster positive personalities towards the social and cultural side of society in the globalization era.